Regime changes and the sustainability of fiscal imbalance in East Asian countries - Evan, Lau; Ahmad Zubaidi, Baharumshah (North-Holland, 2007)
In the aftermath of the 1997 Asian financial crisis, fiscal policy is playing a bigger role in smoothing the business cycle and getting the crisis-affected countries back on their growth paths. The main purpose of this paper is to assess empirically the fiscal policy regimes in five Asian countries using a formal framework based on the government’s intertemporal budget constraints (GIBC). For this purpose, we relied on an array of time-series methods and quarterly frequency data of nearly three decades that ended in 2003:Q2. Our conclusions are; first, the evidence indicates that the fiscal stance in Thailand and Korea are on their sustainable path while the Philippines and Malaysia satisfy only the necessary condition for sustainability. Second, we found that revenues are growing at a rate faster than government spending for Singapore, a country that have recorded large surpluses for most of the sample period. Third, the results show a one-way causation from expenditure to revenue for Korea, Singapore and Thailand. This finding indicates that reducing the size of government spending may improve fiscal budget deficits without having to undergo changes in the overall strategy. Fourth, we observed a long-run feedback causality in the evenueexpenditure nexus for the case of Malaysia and the Philippines, which may require fiscal synchronization instrument policies to moderate the post-crisis fiscal imbalances. Together, these results demonstrate the diverse fiscal patterns but they should be useful as a means of understanding the complexities of economic integration in the region.